2008
DOI: 10.1590/s0103-166x2008000300004
|View full text |Cite
|
Sign up to set email alerts
|

Triagem cognitiva: comparações entre o mini-mental e o teste de trilhas

Abstract: Este estudo investigou o desempenho de idosos no teste de triagem cognitiva Mini-Mental. Comparando a performance de 92 idosos neste teste e no Teste de Trilhas, demonstrou-se que o teste de triagem cognitiva Mini-Mental não é adequado para identificar comprometimento cognitivo precoce. Embora as análises realizadas tenham demonstrado que os idosos com pior desempenho no Teste de Trilhas tiveram performance inferior no teste de triagem cognitiva Mini-Mental, sujeitos que acertaram o primeiro se saíram melhor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 11 publications
0
9
0
14
Order By: Relevance
“…Such data is in line with the study by Paulo and Yassuda (11) . There was no increase in the MAC-Q score correlated to the participants' age, according to the studies of Lima-Silva and Yassuda (20) and Mota et al (10) , in which older participants did not show worse performance or more memory complaints. However, in our research we observed the correlation between the duration of the complaint with MAC-Q and negative memory perception, since the longer the time of memory complaint, the worse its perception.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Such data is in line with the study by Paulo and Yassuda (11) . There was no increase in the MAC-Q score correlated to the participants' age, according to the studies of Lima-Silva and Yassuda (20) and Mota et al (10) , in which older participants did not show worse performance or more memory complaints. However, in our research we observed the correlation between the duration of the complaint with MAC-Q and negative memory perception, since the longer the time of memory complaint, the worse its perception.…”
Section: Discussionmentioning
confidence: 78%
“…Such aspect is due to knowing that the decline will affect the performance of daily life activities, generating great impact on social and occupational activities of individuals (9) . Thus, early identification of cognitive decline may help to create strategies to promote cognitive activities, in order to slow the impact on the individuals' daily life (10) . Some cognitive deficits involve memory, which is the most frequent cognitive complaint in older people (4) .…”
Section: Introductionmentioning
confidence: 99%
“…There are several Brazilian studies that present TMT data from elderly (Hamdan & Bueno, 2005;Mota, Banhato, Silva, & Cupertino, 2008).…”
Section: Instrumentsmentioning
confidence: 99%
“…Assim, a procura de instrumentos de avaliação, principalmente de triagem cognitiva é fundamental para monitorar mudanças sutis na cognição, a fim de que doenças como a demência sejam identificadas em estágios precoces (MOTA et al, 2008).…”
Section: Introductionunclassified